G-Frames and operator valued-frames in Hilbert C*-modules - Khosravi, A.; Hosseini, S. (Methods of Functional Analysis and Topology, 2011)
g-frames and fusion frames in Hilbert C*-modules have been defined by the second author and B. Khosravi in [15] and operator-valued frames in Hilbert C*-modules have been defined by Kaftal et al in [11]. We show that every operator-valued frame is a g-frame, we also show that in Hilbert C*-modules tensor product of orthonormal basis is an orthonormal basis and tensor product of g-frames is a g-frame, we get some relations between their g-frame operators, and we study tensor product of operator-valued frames in Hilbert C*-modules.